Implementasi Pengembangan Kurikulum yang Adaptif Terhadap Perkembangan Teknologi Pendidikan: Penelitian - M. Efrendi; Wisnu Aji Pangestu; Syafi’i Ma’arif; Faizal Ikhsan Yusuf Bachtiar; Praptiningsih (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The development of technology in education has brought about a significant transformation in the way learning takes place in the modern era. The curriculum, as a fundamental guideline in the learning process, must adapt to meet the demands of the times. The purpose of this study is to describe the implementation of curriculum development that aligns with technological advancements at SMP Muhammadiyah. This research employed a descriptive qualitative method using observation, interviews, and document analysis techniques. The findings indicate that the school has made efforts to adjust its curriculum to technological progress through the implementation of digitally oriented learning, teacher training, and the integration of informatics subjects. The challenges faced include limited facilities, poor internet access, and the readiness of teachers and students in using digital tools. Nevertheless, teachers have taken the initiative to utilize simple applications such as Google Forms, WhatsApp Groups, and interactive PowerPoint presentations to improve learning efficiency. The school’s efforts in developing an adaptive curriculum have proven to enhance students’ motivation and creativity. This study recommends improving teachers’ competencies, providing adequate technological facilities, and strengthening collaboration between schools and the government to create a learning system that is responsive to changes in the digital era.